PENGEMBANGAN MEDIA SUPERMARKET SIMULATION KIT BERBASIS MULTIMODAL PADA MATERI OPERASI HITUNG BILANGAN CACAH UNTUK SISWA KELAS V SEKOLAH DASAR - Siti Raihan; Pagarra, Hamzah; Hamid, Hidayat Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research problem stems from conventional and less contextual learning of whole-number arithmetic, which makes students less active and have difficulty applying concepts to everyday situations. This study aimed to develop a multimodal Supermarket Simulation Kit and determine its feasibility and practicality. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, questionnaires, and documentation. The product was validated by media and subject-matter experts and tested through one-to-one, small-group, and large-group trials. The results showed that the media was feasible according to the media expert and highly feasible according to the subject-matter expert, while student trials and teacher responses were categorized as very good. The multimodal *Supermarket Simulation Kit* provides interactive, contextual, and enjoyable learning through buying-and-selling simulations. Therefore, the media is considered feasible and practical for teaching whole-number arithmetic to fifth-grade elementary school students.